Suboptimal Role of Mediators in Sidoarjo Religious Court: Implications for Divorce Rates: Kurang Optimalnya Peran Mediator di Pengadilan Agama Sidoarjo: Implikasinya terhadap Angka Perceraian - Riska Apriana; Noor Fatimah Mediawati (Academia Open, 2022)
The aim of this normative Juridical research study was to determine the role of mediators in the Sidoarjo religious court in reducing the number of divorce cases. The study found that the role of mediators was less than optimal due to the small number of mediators available, with only 5 mediators responsible for handling thousands of cases. In 2022, however, there was a notable increase in the number of successfully mediated divorce cases, with 91 cases successfully mediated in July and 80 in August. This demonstrates the potential benefits of increasing the number of mediators in the Sidoarjo religious court, as it could lead to more effective mediation and fewer divorces. These findings have important implications for the Sidoarjo Religious Court and suggest that increasing the number of mediators could be a viable strategy for reducing the number of divorce cases. Highlights: The study highlights the suboptimal role of mediators in the Sidoarjo religious court due to the lack of available mediators, with only five mediators responsible for handling thousands of divorce cases. The research demonstrates the potential benefits of increasing the number of mediators in the Sidoarjo religious court, as evidenced by the increasing number of successfully mediated divorce cases in 2022. The findings suggest that increasing the number of mediators could be an effective strategy for reducing the number of divorce cases in Sidoarjo, which has important implications for the Sidoarjo religious court and its efforts to minimize divorce rates. Keywords: mediators, religious court, divorce cases, role effectiveness, increasing number